The Relationship between Work Attitudes, Self- Esteem and Work Performance of Employees at the Construction Industry Company - Rattanaburi, Preecha (JOURNAL OF SOUTHERN TECHNOLOGY, 2018)
The objectives of this research were to study the relationship between their work attitudes and self-esteems and work performance at the construction industry company. The samples of 389 employees were selected from the total number of the employees at the company. A questionnaire with its reliability value of 0.86 was used as the research instrument. The result showed that the employees’ work attitude, self-esteem, and work performance were highly rated. Both work attitudes and self-esteem of these employees were significantly positive related to their work performance. The results of this study indicated that work attitudes and self-esteems were positively correlated. Therefore, administrators should try to maintain their employees’ positive work attitudes and boost their self-esteems to increase their work efficacy and efficiency which lead to success of the company.